The effect of Covid-19 pandemic on regional financial performance in Indonesia: Meta-analysis - Altin, Darus; Vebtasvili, Vebtasvili; Eprianto, Idel (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
This meta-analysis aims to analyze the impact of the Covid-19 pandemic on regional financial performance in Indonesia. The research method used by reviewing, summarizing data and analyzing some research results that have been published on google scholar and the ministry of education and culture's Sinta page with the keywords Covid-19 and regional financial performance. From the 45 articles collected, 18 articles were selected for further analysis according to this research topic. This type of research is a meta-analysis research where the steps taken include: data collection, coding, calculation of improving problem-solving ability and identifying the presence or absence of average differences, and drawing conclusions. Our findings show that Covid-19 pandemic in Indonesia has been shown to have an impact on regional financial performance in Indonesia. Although there are several provinces in Indonesia, it does not have an impact on its financial performance. Financial performance is measured from the regional financial independence, the ratio of local tax to paid allowance, the ratio of operational solvency of local governments, the ratio of pad effectiveness and capital expenditure. There is a budget policy from the central government to focus on handling the Covid-19 pandemic so that it impacts regional financial performance. Future research contributions are expected to be an opportunity for the development of research methodologies, especially in the aspect of data collection through questionnaires and data analysis techniques using PLS (Partial Least Square), Data Panel Analysis and Symbolic Interaction methods.